USE OF MANAGEMENT CONSULTING TOOLS IN THE MANAGEMENT OF A SMALL ENTERPRISE - В. В. Лаптєва (Ринкова економіка: сучасна теорія і практика управління, 2018)
The conditions of successful development of a modern small enterprise, which are contained in the ability to warn the market demand for products and services due to the ability to undergo organizational transformation within the life cycle of an economic entity, are shown. It is emphasized that the need for managerial counseling is exacerbated when the managerial potential of a small enterprise is not sufficient to solve the accumulated problems. The object of management consulting is a small enterprise that wants positive changes in the results of its own activities, and the subject - the managerial attitudes and way of thinking of subjects of holistic behavior, that is, managers, owners, workers.